The Effectiveness of Government Regulation of the Republic of Indonesia Number 11 of 2017 Concerning the Management of Civil Servants on the Discipline Level of Government Employees - Andi Pattarani; Lina Mariana; Hidayat Marmin; Aditya Halim Perdana Kusuma Putra (International Journal of Artificial Intelligence Research, 2022)
The aims of this research are: (1) To know and analyze the effectiveness of Government Regulation no. 11 of 2017 concerning the management of civil servants for employee discipline in the Palopo City Government; and (2) to know and analyze the factors that influence the effectiveness of the implementation of Government Regulation No. 11 of 2017 concerning the management of civil servants for employee discipline in the Palopo City Government. This research is descriptive research with an empirical approach. The descriptive research method uses primary data with data collection techniques such as documentation, interviews, and questionnaires. The population in this study were all employees in the Municipal Government of Palopo. The sample in this study was determined to be as many as 45 respondents using a purposive sampling technique. The results of the survey show that: (1) Government Regulation Number 11 of 2017 concerning the Management of Civil Servants for employee discipline in the Palopo City Government is implemented ineffectively which is generally considered to be less effective, especially those rules contained in Article 229, namely: (1) To ensure the maintenance of order in the smooth implementation of their duties, civil servants must comply with civil servant discipline; (2) Government agencies are required to enforce discipline against civil servants and carry out various efforts to improve discipline; (3) Civil servants who commit disciplinary violations are subject to disciplinary punishment; (4) Disciplinary punishment for civil servants is imposed by officials who have the authority to punish; and (2) PNS quality factors, PNS behavior, PNS welfare, legal structure, legal culture, legal knowledge, and legal sanctions affect the ineffective implementation of Government Regulation Number 11 of 2017 concerning Management of Civil Servants towards employee discipline in the Palopo Municipal Government, so that the implementation of these seven factors needs to be maximized